Characterization of resistance to Cephus cinctus Norton (Hymenoptera: Cephidae) in barley germplasm - Varella, Andrea C.; Talbert, Luther E.; Achhami, Buddhi B.; Blake, Nancy K.; Hofland, Megan L.; Sherman, Jamie D.; Lamb, Peggy F.; Reddy, Gadi V. P.; Weaver, David K. (My University, 2018)
Most barley cultivars have some degree of resistance to the wheat stem sawfly (WSS), Cephus cinctus Norton (Hymenoptera: Cephidae). Damage caused by WSS is currently observed in fields of barley grown in the Northern Great Plains, but the impact of WSS damage among cultivars due to genetic differences within the barley germplasm is not known. Specifically, little is known about the mechanisms underlying WSS resistance in barley. We characterized WSS resistance in a subset of the spring barley CAP (Coordinated Agricultural Project) germplasm panel containing 193 current and historically important breeding lines from six North American breeding programs. Panel lines were grown in WSS infested fields for two consecutive years. Lines were characterized for stem solidness, stem cutting, WSS infestation (antixenosis), larval mortality (antibiosis), and parasitism (indirect plant defense). Variation in resistance to WSS in barley was compared to observations made for solid-stemmed resistant and hollow-stemmed susceptible wheat lines. Results indicate that both antibiosis and antixenosis are involved in the resistance of barley to the WSS, but antibiosis seems to be more prevalent. Almost all of the barley lines had greater larval mortality than the hollow-stemmed wheat lines, and only a few barley lines had mortality as low as that observed in the solid-stemmed wheat line. Since barley lines lack solid stems, it is apparent that barley has a different form of antibiosis. Our results provide information for use of barley in rotation to control the WSS and may provide a basis for identification of new approaches for improving WSS resistance in wheat.